Sexual dimorphism in Apfelbeckia insculpta (L. Koch, 1867) (Myriapoda: Diplopoda: Callipodida) - Ilić, Bojan S.; Mitić, Bojan M.; Makarov, Slobodan E. (Archives of Biological Sciences, 2016)
Apfelbeckia insculpta (L. Koch, 1867) is one of the largest European millipedes and an endemic species of the Balkan Peninsula. We present data on sexual dimorphism in size and body proportions obtained from 179 adult specimens of this species from four caves in Serbia and one in Montenegro using univariate and multivariate morphometric techniques. Sexual dimorphism was apparent and female-biased for all measured characters, except for lengths of the antennae and the 24th leg pair (which were larger in males) and lengths of the first, second and fourth leg pairs, which exhibited small differences between sexes. Generally, females had significantly greater body size than males, while males expressed significantly greater values in traits that can be associated with mobility and copulation behavior. Also, we found significant variations in sexual size and body proportions dimorphism among analyzed populations. The influences of fecundity and sexual selection on the adult body plan in A. insculpta are discussed. DOI: 10.2298/ABS160229060I Received: February 29, 2016; Revised: May 5, 2016; Accepted: May 18, 2016; Published online: July 27, 2016 How to cite this article: Ilić B, Mitić B, Makarov S. Sexual dimorphism in Apfelbeckia insculpta (L. Koch, 1867) (Myriapoda: Diplopoda: Callipodida). Arch Biol Sci. 2017;69(1):23-33.